The Nigeria’s Presidentialism and the Burden of Profligacy in an Inchoate Constitutional Democracy - Awotokun, Kunle (Mediterranean Journal of Social Sciences, 2020)
The Nigeria’s presidential democracy has largely failed to meet the yearnings of the people. The government is deficit in the much-needed infrastructural development. Indeed, most of the existing institutions are in a state of coma. A cursory examination of the political architecture depicts waste coupled with high cost of governance at all tiers of government namely local, state and federal. The cost of running presidential democracy is astronomically high bordering on extravagance in a country that is riddled with mass poverty, youth unemployment resulting in insecurity of life and property, kidnapping, armed robbery, banditry etc. The question is how can the state arrest waste and channel human and material resources towards projects that can impact positively on the socio-economic well-being of the citizenry. This work will respond to these interrogations. The paper will employ secondary data such as journals, books, magazines and periodicals to elicit information necessary for its analysis.